Family Psychological Responses in Implementing Booster Vaccination for COVID-19 in Schizophrenia as a Prevention of Covid-19 based on Positive Mental Health (PMH) - M. Suhron; M. Hasinuddin; Faisal Amir; Sitti Sulaiha (Universitas STRADA Indonesia, 2024)
Background: Positive mental health (PMH) response for families who have schizophrenic patients in the implementation of vaccination is a double burden that occurs in efforts to prevent the Covid-19 Virus in schizophrenic patients. Purpose: The study aims to explain Family Psychological Responses to the implementation of booster vaccination in Schizophrenia as a Prevention of Covid-19 based on PMH. Methods: This means Between October and December 2022, there will be 127 families with schizophrenia-afflicted members. This study used a sequential explanatory design with a mixed methodology. PMH scale instrument was employed as the research tool in a community-based adult with the PMH scale's sensitivity. Results: Results of the study findings revealed that the overall PMH questionnaire of PMH scale included 6 items 1) General coping Rural (2.99 ±1.2); Urban (2.27 ±1.1) 2) Emotional support Rural (2.99±1.2); Urban (2.27 ±1.1); 3) Spirituality, Rural (2.99±1.8); Urban (2.29 ± 1.3), 4) Interpersonal Skill highest score Rural (2.99 ± 1.2); Urban (2.27 ±1.1), 5) Personal Growth & Autonomous Rural (2.99 ±1.2); Urban (2.27 ±1.1), 6) Global Affect Rural (2.98 ±1.6); Urban (2.28 ±1.1). Conclusion: PMH psychological responses can occur in the implementation of booster vaccination in families of schizophrenia patients so Along with PMH, Negative Mental Health, and vaccination implementation in families of schizophrenia patients, it is important to pay attention to both (NMH).